ECHIPA „HASDEU”: ELEMENTE CONSTITUTIVE ŞI DISTRUCTIVE ÎNTR-O ECHIPĂ - KULIKOVSKI, Lidia (BIBLIOPOLIS, 2020)
The constituion of the team is a very hard thing, sometimes impossible. One of the institutional value assumed by the Municipal Library is the teamwork. The insistent and consequent activity bild and estableshed this value in our community. We thought that it would work permanently. But the team must be maintained, improved, developed. I believe that actions were not enough. The impediments like lack of confidence and of commitment, fear of conflict, avoinding of responsabilities, lack of attention to the results created some team disfunction. Successful teams do not forget trust, conflict, commitment, accountability and focus on results. A consolidation element of our team is the anniversary of the library foundation together with other activities such as the City quest and the Summer Colocvium.